Sectoral Analysis of Hungarian Professional Football Clubs - Hungarian Football Money League 2014-2016 - Bácsné Bába, Éva; Bács, András Bence; Bács, Zoltán (International Journal of Engineering and Management Sciences, 2018)
Based on the model of the Deloitte Football Money League we recreated the „Hungarian Football Money League”, which gathers and analyses the most economically powerful Hungarian football enterprises. The model gave us an oppurtunity to analyse and compare the industry to the international level. With the hungarian professional football-enterprises we assume, the most economically powerful teams play in the NB. I. (National Championship). Because of this reason we only analysed NB 1. club teams. From the 12 participating team we selected only those 9 who stayed in the League for three consecutive years. The implications from this study is that the hungarian club teams stays well below the international level, altought top level enterprises' joint economical impact is indeed significant in the hungarian sportsector.